Monodisperse polysarcosine-based highly-loaded antibody-drug conjugates. Issue 14 (12th March 2019) - Viricel, Warren; Fournet, Guy; Beaumel, Sabine; Perrial, Emeline; Papot, Sébastien; Dumontet, Charles; Joseph, Benoît
Abstract : A new antibody-drug conjugate (ADC) chemical drug-linker platform based on polysarcosine enables increased drug-loading, improved pharmacokinetics and exquisite in vivo potency. Abstract : Antibody-drug conjugates (ADCs) convey highly potent anticancer drugs to antigen-expressing tumor cells, thereby sparing healthy tissues throughout the body. Pharmacokinetics and tolerability of ADCs are predominantly influenced by the drug-antibody ratio (DAR) of the conjugates, which is to-date limited to a value of 3–4 drugs per antibody in ADCs under clinical investigations. Here, we report the synthesis of monodisperse ( i.e. discrete) polysarcosine compounds and their use as a hydrophobicity masking entity for the construction of highly-loaded homogeneous β-glucuronidase-responsive antibody-drug conjugates (ADCs). The highly hydrophilic drug-linker platform described herein improves drug-loading, physicochemical properties, pharmacokinetics and in vivo antitumor efficacy of the resulting conjugates.